2021
DOI: 10.35308/jpt.v8i1.2557
|View full text |Cite
|
Sign up to set email alerts
|

Kondisi Ekosistem Terumbu Karang Di Perairan Krueng Raya, Kabupaten Aceh Besar

Abstract: This study aims to analyze the condition of the coral reef ecosystem including the substrate, genus composition, and the level of coral mortality in the waters of the Malacca Strait, Masjid Raya District, Aceh Besar District. The research was conducted from October 2016 to October 2019 in the waters of the Malacca Strait, Masjid Raya District, Aceh Besar District. The research site is divided into three stations consisting of Lhok Mee Station, Ahmad Rhang Manyang and Benteng Inong Balee Station. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
1
4
1
Order By: Relevance
“…In other words, the abundance of Chaetodontidae fish is not caused by the influence of coral cover conditions but is caused by other indicators not examined in this study. Similar to the research conducted by [14] in the waters of the Spermonde Islands, South Sulawesi that the abundance of Chaetodontidae fish is not affected by coral cover.…”
Section: Relationship Of Chaetodontidae Fish Abundance With Coral Coversupporting
confidence: 80%
See 1 more Smart Citation
“…In other words, the abundance of Chaetodontidae fish is not caused by the influence of coral cover conditions but is caused by other indicators not examined in this study. Similar to the research conducted by [14] in the waters of the Spermonde Islands, South Sulawesi that the abundance of Chaetodontidae fish is not affected by coral cover.…”
Section: Relationship Of Chaetodontidae Fish Abundance With Coral Coversupporting
confidence: 80%
“…So far the Research on Chaetodontidae fish in Aceh that has been carried out has only been reported by [12,13], and the absence of further studies on its relationship with coral reefs. On the other hand, Aceh Province is one of the provinces in Indonesia that has coral reef resources with a fairly high associated biota [14].…”
Section: Introductionmentioning
confidence: 99%
“…These results illustrate that the live corals on Gosong Island are in good condition, according to the category defined by Gomez and Yap (1988). The percentage of live coral growth in the Gosong island area tends to be higher than in Unggeh Island Central Tapanuli Regency 12.33-28.54% (Harahap et al, 2019), Mansiman Island area, Manokwari 32.44% (Dasmasela et al, 2019), Iboh 27.76% (Munandar et al, 2019), Bunaken Island 32, 92% (Schaduw et al, 2020), and coastal water of Inong Balee in Aceh Besar 50.31% (Najmi et al, 2021). However, when compared to the condition of coral reefs on the island of Saebus, Sumenep, East Java, (Rizmaadi et al, 2018), the research location has a lower percentage of around 4.2-9.36% and Simeuluecut, Simeulue island of 28.13% (Wisha et al, 2019).…”
Section: Coral Conditionmentioning
confidence: 96%
“…Coral reefs have experienced anthropogenic stress directly or indirectly (Obura et al, 2019). Disturbances in coral reef ecosystems can cause damage to populations and species diversity of reef fish (Najmi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of coral reefs, both identification and cover, are still very limited in the waters of West South Aceh. Several studies related to this topic have been conducted in Aceh everal studies related to this topic have been carried out in Aceh Province, namely Pulau Weh (Rudi et al 2012), Johan Pahlawan and Samatiga, West Aceh (Annas et al 2017), and Krueng Raya, Aceh Besar (Najmi et al 2021). Therefore, it is necessary to conduct studies on the current conditions of coral reefs in the region.…”
Section: Introductionmentioning
confidence: 99%